Case Report: Testicular Torsion in Unilateral Supernumerary Testis - Xiaofei, Lu; Benzhang, Zhou (Frontiers in Pediatrics, 2022)
Supernumerary testis (SNT), or polyorchidism, is a rare congenital anomaly of the genitourinary tract, described as the presence of more than two testicles.And testicular torsion(TT) in unilateral supernumerary testis is extremely rare. We report a case of unilateral supernumerary testis in a 16-year-old boy accompanied by testicular torsion, which was diagnosed preoperatively based on the outcomes of physical examination and ultrasound and conformed intraoperatively. We opted for orchiectomy of this supernumerary testis because of the long-time hypoperfusion. And as for the normal testis, orchidopexy was performed. His clinical presentation subsided after surgery, and the patient was discharged 3 days later.